2002
DOI: 10.1191/0143624402bt031oa
|View full text |Cite
|
Sign up to set email alerts
|

The London Heat Island: results from summertime monitoring

Abstract: The paper presents some aspects of Warsaw's climate, in particular the urban heat island. UHI changes in different seasons and in different air mass types were analysed over the years 2011-2012. Average UHI in Warsaw is of a diamond shape which reflects the distribution of the densest built area and exceeds 2.0°C in the city centre compared to the airport station. In subtropical air mass, the intensity of UHI on the left side of the Vistula River reached 7.7°C. The basis for the analysis is the microclimatic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 9 publications
6
57
1
Order By: Relevance
“…Temperature data for London in the period 1931-1960 reported a mean annual UHI for central London of 1.48C (1.68C in summer and 1.28C in winter). 6 Watkins et al 7 measured the UHI of London during 1999. They found that the UHI decreased approximately as 1/r 2 , (where r is the radial distance from the thermal centre) and was about 2.88C on average, with values as high as 78C recorded on some days.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature data for London in the period 1931-1960 reported a mean annual UHI for central London of 1.48C (1.68C in summer and 1.28C in winter). 6 Watkins et al 7 measured the UHI of London during 1999. They found that the UHI decreased approximately as 1/r 2 , (where r is the radial distance from the thermal centre) and was about 2.88C on average, with values as high as 78C recorded on some days.…”
Section: Introductionmentioning
confidence: 99%
“…London's UHI is well described (for example, Howard 1818; Watkins et al 2002;Kolokotroni and Giridharan 2008;Bohnenstengel et al 2011;Mavrogianni et al 2011), and the nocturnal summertime UHII has been shown to be approximately 2 • C (Kolokotroni and Giridharan 2008). During periods of extreme weather, for example, the 2003 heat wave, parts of central London were up to 10 • C warmer than the surrounding rural zone (GLA 2010).…”
Section: London's Uhimentioning
confidence: 99%
“…The annual mean air temperature within a large city can be more than 2°C higher than in nearby rural areas (e.g. Watkins et al 2002). In the evening and at night, the UHI intensity can be much higher (as much as 10°C), as well a b as air temperature differences between city areas with different building structures (Buchholz and Kossmann 2015).…”
Section: Temperature Extremesmentioning
confidence: 99%